Results From A Comprehensive Global Navigation Satellite System Test In The CORS-TR Network: Case Study - Eren, Kamil; Uzel, Turgut; Gülal, Engin; Yıldırım, Ömer; Cingöz, Ayhan (Asce-Amer Soc Civil Engineers, 1801 Alexander Bell Dr, Reston, Va 20191-4400 Usa, 2009)
This paper presents one of the most comprehensive tests conducted about the real-time kinematics (RTK) and continuously operating reference stations (CORS) network using instruments from three global positioning system (GPS) manufacturers (Leica, Topcon, and Trimble). The test was carried out between August and October 2006 in the Marmara Region of Turkey as part of the research project for establishing RTK CORS network covering all of Turkey. Three GPS networks (NET-120, NET-90, and NET-60) were designed, each consisting of six CORS points: with interstation distances of 120, 90, and 60 km, respectively. Leica, Trimble, and Topcon directly participated in the tests, each company contributing a 2 week effort. RTK surveys were compiled at check points (previously known points) and new points were generally selected in built-up areas. Flachen Korrectur parameter-Spatial correction parameters, virtual reference stations, pseudoreference stations, and master auxiliary concept techniques were used for RTK positioning. Postprocessing by network solution software was also used at check points. The results of network-based RTK and postprocessing were found to be successful at each net, the main exception being the difficulties encountered by one of the firms participating at NET-120. Results are discussed in the paper.
Keywords: GPS